2005
DOI: 10.1148/radiol.2371041506
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Tensor MR Imaging of Corticospinal Tract in Amyotrophic Lateral Sclerosis and Progressive Muscular Atrophy

Abstract: Diffusion-tensor MR imaging reveals corticospinal tract impairment in ALS but not in PMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
84
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 51 publications
(39 reference statements)
23
84
0
1
Order By: Relevance
“…Unique imaging characteristics on magnetic resonance spectroscopy, functional magnetic resonance imaging, and 18 Ffludeoxyglucose positron emission tomography may aid in diagnosis [61][62][63][64]. Findings on diffusion tensor imaging also correlate with ALS phenotypes [59], disease severity scales, and disease duration [60].…”
Section: Retigabine: a Case Study For Innovative Als Clinical Trial Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Unique imaging characteristics on magnetic resonance spectroscopy, functional magnetic resonance imaging, and 18 Ffludeoxyglucose positron emission tomography may aid in diagnosis [61][62][63][64]. Findings on diffusion tensor imaging also correlate with ALS phenotypes [59], disease severity scales, and disease duration [60].…”
Section: Retigabine: a Case Study For Innovative Als Clinical Trial Dmentioning
confidence: 99%
“…Modern imaging modalities such as diffusion tensor imaging [59,60], magnetic resonance spectroscopy [61,62], functional magnetic resonance imaging [63], and 18 Ffludeoxyglucose positron emission tomography [64,65] are emerging as potential biomarkers of disease progression. Unique imaging characteristics on magnetic resonance spectroscopy, functional magnetic resonance imaging, and 18 Ffludeoxyglucose positron emission tomography may aid in diagnosis [61][62][63][64].…”
Section: Retigabine: a Case Study For Innovative Als Clinical Trial Dmentioning
confidence: 99%
“…5,6 Most DTI studies in ALS have been limited to the assessment of the CST damage. 7 Whether on the basis of regions of interest, [8][9][10][11][12][13][14][15][16] voxel-based analysis, [17][18][19][20] or tractography, [21][22][23] DTI studies in ALS have shown reduced FA along the CST.…”
mentioning
confidence: 99%
“…The application of DWI is based on the principle that water molecules could explore tissue structures at a microscopic scale which is surpass the ordinary image resolution in the process of their random diffusion-driven displacements (Le Bihan et al, 2001;Cosottini et al, 2005). Water diffusion is known as a three-dimensional procedure which could be quantified via the measurement of the mean diffusivity (MD), the average apparent diffusion coefficient (ADC) along three orthogonal directions (Basser and Jones, 2002).…”
Section: Introductionmentioning
confidence: 99%